Representation of Beauty Standard on Indonesia’s Woman Bankers - Sofy Fawzia Munafidsyah; Sri Kusumo Habsari; Ismi Dwi Astuti Nurhaeni (International Journal of Science and Applied Science: Conference Series, 2022)
The term good-looking is still used in the labor recruitment process in recent years. Especially in the recruitment of bank employees in Indonesia. Bank employees in Indonesia often get the stereotype that "bank staff must be beautiful”. So, this study describes the representation of good-looking bank employees in Indonesia. From this representation, this study also explains that the term good-looking is a term that practices beauty standards in society. This study used qualitative methods and took the data from informal conversations with several informants. In this study, researchers applied the theory of post-feminism, namely beauty myth, and also used Foucault's theory of power relations. The results of this study show that some banking agencies do facilitate their employees in caring for and maintaining physical appearance. It also proves that a good-looking bank employee is according to social beauty standards (ideal height and weight, langsat skin, makeup, and others). This proves that the standard practice of beauty in women is still thriving in society, even in a job or career, not in the entertainment field.